2007
DOI: 10.1080/01904160701615509
|View full text |Cite
|
Sign up to set email alerts
|

Response of Mature Phosphorus-Deficient Apple Trees to Phosphorus Fertilization and Liming

Abstract: The aim of the study was to examine response of mature phosphorus (P) deficient apple (Malus domestica Borkh.) trees to phosphorus fertilization and liming. The experiment was carried out during 2003-2005 in a commercial orchard in Central Poland on 'Jonagold' apple trees/M.26 planted in 1996 on a coarse-textured soil with low both pH (4.6) and organic matter (1.2%). Calcium-lactate soluble phosphorus concentration in the soil was within an optimal range despite appearance of leaf phosphorus deficiency symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…4). The measured values were similar to those in 'Jonagold' apple leaves reported by Wojcik and Wojcik (2007). The foliar application of the Pho Ca significantly increased the amount of P in the leaves of the treated apples.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…4). The measured values were similar to those in 'Jonagold' apple leaves reported by Wojcik and Wojcik (2007). The foliar application of the Pho Ca significantly increased the amount of P in the leaves of the treated apples.…”
Section: Resultssupporting
confidence: 87%
“…1). The improvement in the apple skin color as a result of foliar sprays of P-containing compounds has also been documented in several apple cultivars, including 'Starking Delicious' (Gómez-Cordovés et al, 1996;Larrigaudiere et al, 1996), 'Fuji' (Li et al, 2002), 'Elstar' (Funke and Blanke, 2006), and 'Jonagold' (Wojcik and Wojcik, 2007). In the first three cited studies, the positive effect of foliar P applications on the fruit color was related to increased skin anthocyanin concentration, whereas in the studies of Funke and Blanke (2006) and Wojcik and Wojcik (2007), the apple color improvement was evaluated with the percentage of red blush.…”
Section: Discussionmentioning
confidence: 92%
“…I). A positive infl uence of phosphorus and calcium on apple color has been reported in diff erent cultivars, such as 'Starking Delicious' (Gomez-Cordoves et al, 1996;Larrigaudiere et al, 1996), 'Fuji' (Li et al, 2002), 'Elstar' (Funke and Blanke, 2006) and 'Jonagold' (Wojcik and Wojcik, 2007). Our results of Phostrade Ca sprayings on anthocyanin synthesis are comparable to the results of Li et al (2002), who reported improved red skin color and an increase in fl avonoid content in apples, sprayed with Senifos (a mixture of P, K and N).…”
Section: Resultssupporting
confidence: 79%
“…Conversely, the content of P in the apple fruit affects many physical and chemical attributes related to fruit quality and conservation such as reductions in incidence of water core at harvest, increased resistance to browning, elevated antioxidant content of fruit (NEILSEN et al, 2008), and increased fruit appearance and storability (WOJCIK & WOJCIK, 2007). In addition, spraying apple trees with P increased the contents of this nutrient in the fruit and decreased the loss of flesh firmness (WEBSTER & LIDSTER, 1986) and the susceptibility caused by low temperatures (JOHNSON & YOGORATNAM, 1978).…”
Section: Soil Sciencementioning
confidence: 99%